2021
DOI: 10.3390/molecules26237142
|View full text |Cite
|
Sign up to set email alerts
|

Expression, Purification and Characterization of a Novel Hybrid Peptide CLP with Excellent Antibacterial Activity

Abstract: CLP is a novel hybrid peptide derived from CM4, LL37 and TP5, with significantly reduced hemolytic activity and increased antibacterial activity than parental antimicrobial peptides. To avoid host toxicity and obtain high-level bio-production of CLP, we established a His-tagged SUMO fusion expression system in Escherichia coli. The fusion protein can be purified using a Nickel column, cleaved by TEV protease, and further purified in flow-through of the Nickel column. As a result, the recombinant CLP with a yie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 47 publications
1
7
1
Order By: Relevance
“…Hoelecher et al discovered that fusion to SUMO does not appreciably affect the activity of AMPs [58]. Compared with SUMO-C-L, cecropin-like antimicrobial peptide KR12AGPWR6, and hybrid peptide CLP [57,[59][60][61], our hybrid peptide CAD-Con was also expressed normally and exhibited antifungal activities after purification.…”
Section: Discussionmentioning
confidence: 80%
“…Hoelecher et al discovered that fusion to SUMO does not appreciably affect the activity of AMPs [58]. Compared with SUMO-C-L, cecropin-like antimicrobial peptide KR12AGPWR6, and hybrid peptide CLP [57,[59][60][61], our hybrid peptide CAD-Con was also expressed normally and exhibited antifungal activities after purification.…”
Section: Discussionmentioning
confidence: 80%
“…Like the multidomain approach, segments (but not the full active sequence) of an HDP can be stitched together in a hybrid molecule that is a mix of the parental peptides, a process we named HDP fragment-stitching . Fragments of peptides such as the human cathelicidin LL-37, CM4 from a Chinese domestic silk moth and TP5, a fragment of the thymus hormone, have been used in one study to create hybrid antimicrobial that works against enterotoxic E. coli [ 105 ]. Fragment-stitching might be useful to remove undesired activities from a parental peptide, such as the hemolytic activity of LL-37, while generating new HDPs.…”
Section: Strategies To Optimize Hdp Productionmentioning
confidence: 99%
“…Peptide hybridization is a simple and effective strategy to obtain novel AMPs with higher antibacterial and lower cytotoxicity than parent peptides [ 16 , 17 , 18 ]. CM4, LL37, and TP5 are the parent peptides for our rational design.…”
Section: Introductionmentioning
confidence: 99%
“…The superlative approach to solving this issue is by heterologous expression technology. In our previous work, we expressed a peptide termed CLP fused with a SUMO tag and demonstrated that the purified CLP had antibacterial activity [ 17 ]; however, the protein purified from bacteria still requires expensive LPS removal before clinical application. This has led us to seek other expression platforms.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation